Evaluation of tourist landscape quality in the Qadmus area in Tartous governorate (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Landscapes vary spatially, and human factors and altitude greatly affect the aesthetics of the natural tourist elements. The research discusses determining the aesthetic value of the landscape and studying some of the natural and human factors that affect the aesthetic of the tourist site, which go beyond traditional ideas in limiting them as resources and tourist attractions and studying them as an integrated structure or as a landscape resulting from the terrain and vegetation cover and some other uses of the land that can be positive or negative in its effect on the landscape. The research aims to propose a methodology for evaluating the aesthetic characteristics of the landscape, by applying it to the Qadmous area in Tartous Governorate, using geographic information systems (GIS), according to four factors: Vegetation cover, water resources, industrial facilities, road network. Evaluate the degree of contribution of each factor, positively or negatively, to the aesthetic of the landscape, and determine the weights of the factors according to the importance of each factor to produce the final evaluation map and categorize them into five categories. The research also dealt to determine the viewshed from random points of different heights based on horizontal and three-dimensional simulation models.